Pemikiran Ahmad Mustain Nasoha Tentang Regulasi Kecerdasan Buatan (AI) dalam Perspektif Etika Kewaganegaraan: Ahmad Mustain Nasoha’s Thoughts on Artificial Intelligence (AI) Regulations from a Civic Ethics Perspective - Muhammad Zaidaan Azhar; Gilang Bagistama Islamy; Nabila Azahra Nugraheni; Aurelia Dwi Kumala (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The development of Artificial Intelligence (AI) has brought about massive transformations in modern society. However, behind the opportunities it offers, there are complex ethical, legal, and citizenship challenges. This article examines the challenges of AI regulation from the perspective of Citizenship Ethics, referring to the thoughts of Ahmad Muhammad Mustain Nasoha, who emphasizes the importance of Pancasila as an ethical foundation to guide technological development. Using a qualitative approach through literature study, this article examines the role of AI in shaping digital citizenship behavior, the risks of technology abuse, algorithmic bias, and the urgency of regulation based on the values of social justice, unity, and deliberative democracy. The results of the study show that AI regulation is not only a technical issue, but also relates to morality and national identity. Therefore, ethical and Pancasila-based regulation is considered a strategic solution to ensure that AI becomes a tool that strengthens Indonesian citizenship values in the era of globalization.